Surgical options in treating patients with primary hyperparathyroidism - Majcen, Maša (Radiology and oncology (Ljubljana), 2020)
Background. Primary hyperparathyroidism is the third most common endocrine disorder for which surgical procedure called parathyroidectomy is the most effective treatment. Since the early 20th century, parathyroid surgery has improved extensively. With the advances in preoperative imaging and with understanding the causes of disease, new and minimally invasive surgical approaches overrode the standard bilateral exploratory operations. Directed parathyroidectomy is currently the standard technique for treatment of primary hyperparathyroidism worldwide. Conclusions. Surgery is the only definitive treatment of primary hyperparathyroidism. The most appropriate type of surgical procedure depends on the number and localization of the hyperactive parathyroid glands, availability of modern imaging techniques, limitation of each type of procedure and expertise.
Keywords: kirurško zdravljenje; paratiroidektomija; primarni hiperparatiroidizem